Preparation of Fine Hydroxyapatite (HA) Powder And Its Characterization As Ceramic Biomaterial - Abd Aljabbar, S.; Rahmatallah, S.S.; Al- Sarraf, A.; Shehap, Z.; Dumbous, H. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Biomimatic basic calcium phosphate ,known as Hydroxy apatite(HA), was synthesised using calcium acetate and disodium phosphate dilute hot (boiling) solution of both salts were added slowly to each other. A colloidal suspension formed was aged for few days, then boiled for one hour to induced setting and coagulation of preapatite, and left to cool until they reached room temperature. The precipitate was filtered and washed with distilled water, then ethanol and dried. The dried sample was calcined at 1100 o C.The obtained solid lumps were then crushed reground fine powder and analyzed for calcium to phosphorous ratio. X-ray analysis was carried out to examine the solid sample. Chemical analysis for phosphorus and calcium had been carried out using standard method. The results proved that the calcined sample used in this investigation where Hydroxyapatite .